Resonant tunneling diode integrated with metalens for high-directivity terahertz waves. (7th July 2021) - Endo, Kota; Sekiya, Masashi; Kim, Jaeyoung; Sato, Kento; Suzuki, Takehito
Abstract: Terahertz flat optics based on our originally developed low-reflection metasurface with a high refractive index can offer attractive two-dimensional optical components for the manipulation of terahertz waves. However, it remains to be shown whether a planar collimating metalens made with our original metasurface could be mounted on a resonant tunneling diode with a short distance. Here, we demonstrate that a collimating metalens with a distance of 1.0 mm from the RTD enhances the directivity to 3.0 times at 0.312 THz. The proposed metalens would be integrated with various terahertz continuous-wave sources for emerging industry such as 6 G (beyond 5 G) communications.